Strategie zarządzania czystością seksualną na przykładzie amerykańskiego ewangelikalnego poradnika dla adolescentów. Studium przypadku - Wiktorowski, Grzegorz (Instytut Socjologii Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to show the discursive strategies used in the guides on dating and sexuality for adolescents written from evangelical perspectives and, therefore, religious ones. Applying a specific mode of justification and argumentation as well as specific rhetorical means as persuasive means, the authors create a narrative to encourage adolescent youth to refrain from taking sexual activity and maintaining purity until their wedding day. This last category is defined in several important aspects, which can be described as moral-ethical, sacral, psychological and therapeutic, which refer to the contexts that medicalized attitudes and morals. The analysis of the material allows to understand the formation of the religious cognitive universe and the causal models to which it refers. This allows to construct educational and communication strategies with religious communities in a practical way, which is extremely important in a pluralistic and democratic society.
Keywords: sexuality; adolescent guide(book); [sexual] purity; Evangelicalism